Medical grand rounds in Riyadh, Saudi Arabia: Current attitudes and barriers - Mohammad Alqahtani; Nora Al Balawy; Salih A Bin Salih; Abdullah Al Sayyari; Hanan Al Shammari; Mohammed AlGhobain; Naji Aljohani (Wolters Kluwer Medknow Publications, 2015)
Background: Medical grand rounds (MGRs) are considered key educational tools in most academic medical institutions. In this multi-center cross-sectional survey, we tried to determine the current attitudes of local medical practitioners to MGRs, as well as perceived barriers. Methodology: A total of 120 physicians from the National Guard Hospital, King Fahad Medical City, King Khalid University Hospital and King Faisal Specialist Hospital participated in the survey. The questionnaire consisted of statements on attitudes and perceived barriers against participating in MGRs, as well as participants' levels of agreement. Results: Most participants attend MGRs regularly (94.2%), claiming that it is mandatory (88%). Participants also agreed that MGRs were important tools for continuing medical education (89.2%) and that they provided an opportunity to both present materials and interact with their colleagues in other divisions (86.7% and 81.6%, respectively). The vast majority of respondents agreed that "topic review/update" and "inviting guest speakers" were the two most preferred suggestions for improving MGRs (94.2% and 92.5%, respectively). Major barriers included constraints of time (43.3%) and topics that were not patient-related (40.8%). Conclusion: MGRs in the major Tertiary Hospitals in Riyadh are well attended, and the majority of the local practitioners believe in the positive effect of MGRs in delivering quality and up to date medical knowledge. Time and physician-specific issues were identified as major barriers that needed to be addressed in order to maximize participation of medical staff.